Religious congregations and crime incidents: opportunity and bias - Ulmer, Jeffery T. (Journal of crime and justice, 2020)
Religious congregations’ experiences with crime victimization are an under-researched and poorly understood phenomenon. Religious congregations represent a street crime target as a potential source of money, electronics, furniture and other goods, or as places where potential victims come and go. Furthermore, religious congregations are potential targets of bias crimes, especially certain minority religious traditions. This study examines survey data from a national sample of 1,385 religious congregations to investigate the role of religious tradition, criminal opportunity/routine activities factors, and surrounding structural disadvantage on criminal events experienced by congregations. We examine overall, property, and violent crime. We find that opportunity factors and structural disadvantage foster overall reported crime, as well as property and violent crime separately. By contrast, religious tradition is only associated with violent crime, specifically threats of violence. Jewish and Muslim congregations are more likely to report experiencing violent incidents, and report experiencing them more often.